Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

If a graph of the quadratic function $f(x)=ax^2+bx+c$, where $a$, $b$ and $c$ are constants. If this function vertex is $(13,−169)$ and the distance between the two intersection points with the $x$-axis is $26$, what is the value of $a$, $b$, and $c$?

share|cite|improve this question
Hint: how is the vertex defined and how the two intersection points? – al-Hwarizmi Jul 28 '13 at 13:04
up vote 3 down vote accepted

Knowing the vertex, $(x_0, y_0)$ of a parabola tells us the equation of the parabola can be written as:

$$(y - y_0) = p(x - x_0)^2$$

$$y - (-169) = p(x - 13)^2$$ $$ y + 169 = p(x^2 - 26 x + 169)$$ $$y = p(x^2 - 26x + 169) - 169$$

Now use the fact that a "vertical parabola" (of the form $f(x) = y = ax^2 + bx + c$) intersects the $y$ axis at points which are symmetrical about the line $x = x_0$. For this parabola, we know the vertex is $(x_0, y_0) = (13, -169)$, so $x = x_0 = 13$ is the line of symmetry. Given that the distance between the $x$-intercepts is $d = 26$, the "roots" of the equation $y = 0 = p(x^2 - 26x + 169) - 169$ must be $x_1 = 13 - 13 = 0, x_2 = 13 + 13 = 26$, and solving for $p$ then gives us $p = 1$.

This gives us that $$f(x) = y = p(x^2 - 26x + 169) - 169 \iff f(x) = x^2 - 26x \implies a = 1, b = -26, c = 0$$

share|cite|improve this answer
Clear and concise +1 – Amzoti Jul 29 '13 at 0:59

Use the vertex form of the quadratic:


Where the vertex is $(h,k)$.

$$\begin{align}f(x)&=m(x-13)^2-169 \\ f(x)&=m(x^2-26x+169)-169 \\ f(x)&=mx^2-26mx+(169m-169) \end{align} $$

The distance between zeros on the x-axis of a polynomial in standard form $x^2+bx+c$ is:


Substitute in $a=m$, $b=26m$, $c=169m-169$, and $d=26$, and solve for $m$.

share|cite|improve this answer

There are various ways of solving this. Perhaps the easiest is to note that the "vertex" is the place where the vertical line $x=13$ is a line of symmetry.

The zeros of the quadratic are placed symmetrically either side of this line - so $13$ away on each side, to make the distance between them equal to $26$ - so zeros are $x=0, 26$.

Any quadratic function with these zeros has form $a(x-0)(x-26)=ax(x-26)$

And it should be easy to solve from there.

share|cite|improve this answer

$$y=ax^2+bx+c \implies \left(x+\frac b{2a}\right)^2=4\cdot\frac14\left(y-\left(c-\frac{b^2}{4a}\right)\right)$$

Comparing with $(x-h)^2=4a(y-k)$ the vertex will be $\left(-\frac b{2a},c-\frac{b^2}{4a}\right)$

So, $-\frac b{2a}=13\implies b=-26a\ \ \ \ (1)$

and $c-\frac{b^2}{4a}=-169\implies b^2-4ac=169\cdot4a\ \ \ \ (2)$

$\implies 4ac=b^2-169\cdot4a=(-26a)^2-169\cdot4a$

$\implies c=169(a-1) \ \ \ \ (3)$ assuming $a\ne0$

For the two intersection points with the x-axis, $y=f(x)=0$

If $(x_1,0),(x_2,0)$ are the two intersection points, $x_1,x_2$ are the roots of $ax^2+bx+c=0$

$$\implies x_1+x_2=-\frac ba,x_1x_2=\frac ca$$

So, the distance will be $\sqrt{(x_1-x_2)^2+(y_1-y_2)^2}=\sqrt{(x_1+x_2)^2-4x_1x_2}=\frac{\sqrt{b^2-4ac}}{|a|}=\frac{\sqrt{676a}}{|a|}\text{ using }(2)$

So, the distance $=26\sqrt a$ assuming $a>0$ otherwise the distance will be complex

Then we have $26\sqrt a=26$

Now use $(1),(3)$ to find $b,c$ respectively

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.